2019
DOI: 10.1002/job.2372
|View full text |Cite
|
Sign up to set email alerts
|

Rivals or allies: How performance‐prove goal orientation influences knowledge hiding

Abstract: Summary Previous research suggests that performance‐prove goal orientation is positively related to knowledge hiding. However, we argue that this effect depends on the focus of performance feedback (i.e., individual‐ and group‐focused feedback), which shapes the nature of the competitive expression of performance‐prove goal orientation (i.e., intragroup and intergroup oriented). We conducted three studies to test our theoretical model. The results of Study 1 with time‐lagged data from 128 part‐time MBA student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 100 publications
3
84
0
Order By: Relevance
“…Like the preceding paper, it also contributes to the knowledge hiding literature by suggesting that rationalized hiding, which involves less deception than playing dumb or evasive hiding, may have different antecedents. Zhu, Chen, Wang, Jin, and Wang (2019) explain why and how performance-prove goal orientation predicts increased levels of knowledge hiding. These authors studied the extent to which this effect depends on whether performance feedback is focused on individuals versus groups, which may form a different competitive expression of performance-prove goal orientation.…”
Section: Articlesmentioning
confidence: 94%
See 2 more Smart Citations
“…Like the preceding paper, it also contributes to the knowledge hiding literature by suggesting that rationalized hiding, which involves less deception than playing dumb or evasive hiding, may have different antecedents. Zhu, Chen, Wang, Jin, and Wang (2019) explain why and how performance-prove goal orientation predicts increased levels of knowledge hiding. These authors studied the extent to which this effect depends on whether performance feedback is focused on individuals versus groups, which may form a different competitive expression of performance-prove goal orientation.…”
Section: Articlesmentioning
confidence: 94%
“…Zhu, Chen, Wang, Jin, and Wang () explain why and how performance‐prove goal orientation predicts increased levels of knowledge hiding. These authors studied the extent to which this effect depends on whether performance feedback is focused on individuals versus groups, which may form a different competitive expression of performance‐prove goal orientation.…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have shown that abusive behaviors of supervisors are associated with employees' undesirable attitudinal and behavioral outcomes, such as low job performance [30], a decrease in organizational citizenship behavior [32], an increase in deviant workplace behavior, job burnout, and emotional exhaustion [33][34][35][36][37]. Moreover, prior studies tested several individual (i.e., professional commitment and psychological entitlement) and organizational factors (i.e., organizational culture, policies, leadership styles) as antecedents with KH [12][13][14][15][16][17][18]20]. However, one such undesirable behavioral outcome is KH, which is largely ignored in the abusive supervision literature.…”
Section: Abusive Supervision and Knowledge Hidingmentioning
confidence: 99%
“…Similarly, knowledge-related factors that contribute to KH include task relatedness and complexity of knowledge [6]. Previous research has also explored various organizational factors in relation to KH, including leadership styles, culture, knowledge management system, policies, goal orientation, and politics [16][17][18][19][20]. However, the abusive behaviors of supervisors, which lead to KH behaviors, is not explained fully.…”
Section: Introductionmentioning
confidence: 99%